Foodborne parasites: Outbreaks and outbreak investigations. A meeting report from the European network for foodborne parasites (Euro-FBP) - Cacciò, Simone M.; Chalmers, Rachel M.; Dorny, Pierre; Robertson, Lucy J. (Food and waterborne parasitology, 2018)
Foodborne parasites (FBP) are a neglected topic in food safety, due to lack of awareness of their importance for public health, their biological diversity, and, for many FBP, lack of standardized detection methods, which complicates identification of the infection vehicle. The COST Action FA1408, A European Network for Foodborne Parasites (Euro-FBP), aims to limit the impact of FBP on public health by facilitating multidisciplinary cooperation and partnership among researchers, and between researchers and stakeholders. Outbreaks represent a common topic overarching specialization in one or more FBP, thus providing a platform for knowledge exchange. This report summarizes the outcomes of a meeting within the Euro-FBP consortium entitled ‘Outbreaks and Outbreak Investigations’. Recent and historical outbreaks of trichinellosis, opisthorchiasis, and cryptosporidiosis were used as examples to underline the complexity of the topic, the different foods implicated and their traceability, and the lack of standardized detection methods for some parasites. Possible solutions to overcome current limitations were also illustrated. The meeting provided an opportunity to learn from recent advances in the study of bacterial foodborne outbreaks, with an emphasis on genome analysis. •Foodborne parasitic outbreaks are often difficult to identify and investigate.•Collaboration between local health units and reference labs is essential.•Tracing is difficult, but important for control implementation.•Approaches in use to study bacterial foodborne outbreaks should be applied to FBP.